Impact of weight loss on cardiac function: improvement in left ventricular global longitudinal strain following metabolic surgery. (3rd October 2022) - Hughes, D; Wilson, R; Saijo, Y; Chan, N; Kumar, A; Grimm, R; Griffin, B; Tang, W; Nissen, S; Aminian, A; Xu, B
Abstract: Introduction: Obesity leads to an increased risk of cardiovascular disease (CVD) morbidity and mortality and is associated with the metabolic risk factors such as hypertension, diabetes mellitus, hyperlipidemia [1]. Metabolic surgery has been proven to be the most effective long term weight management tool and has known benefits in CVD prevention [2]. Global longitudinal strain (GLS) is an effective quantitative measurement of left ventricular (LV) function that is also a powerful predictor of future CVD events and mortality [3]. The impact of metabolic surgery on LV structure and function is unknown. Purpose: This study investigated the changes in cardiac structure and function after metabolic surgery, including GLS. To our knowledge there has not been a study investigating this relationship previously reported. Methods: Consecutive patients undergoing metabolic surgery at our center between March 2005 and February 2019 were recruited. Patients with transthoracic echocardiographic imaging (TTE) pre and post metabolic surgery (May 2005 to January 2019) were included. Electronic medical records were searched to obtain demographic, surgical and clinical data. GLS was calculated with Velocity Vector Imaging (VVI, Siemens, v2.0, Pennsylvania, USA). Averaged GLS values were derived from 4 chamber, 2 chamber and 3 chamber calculations. Results: 398 patients with pre- and post-operative cardiac imaging were included. Please see Table 1 for the baseline demographics of our study population. The mean age was 60.0 years with 70% being female. There were significant rates of CVD risk factors such as: hypertension (76.4%), diabetes mellitus (58.8%) and hyperlipidemia (76.4%). The clinical and echocardiographic changes noted post metabolic surgery are detailed in Table 2. Along with decreases in weight post operatively, there were significant improvements in the markers of CVD risk factors such as mean blood pressure (134/75 to 129/72 mmHg, p value <0.001), mean gylcated hemoglobin levels (7.0 to 6.1%, p value <0.001) and mean low density lipoprotein (LDL) levels (97.7 to 88.2 mg/dl, p value <0.001). There were a number of statistically significant positive changes in the left ventricular structure and function. The mean LV ejection fraction increased from 56.3% to 57.4% (p=0.008); left ventricular mass decreased from 238.2 g to 179.3 g (p value <0.001), and both septal and posterior wall thicknesses decreased significantly (p value <0.001). The LV mass indexed to body surface area (BSA) also decreased from 93.5 g/m 2 to 83.1 g/m 2 . The average global LV GLS was −15.7% pre-operatively, improving significantly to −17.9% post-operatively (p<0.001). Conclusion: Our study has shown for the first time the impact of metabolic surgery on ventricular structure and function, with reduction in LV mass and improvement in LV GLS. These novel findings lends further support to the cardiovascular benefits of metabolic surgery. Funding Acknowledgement: Type of funding sources: None.